Interfacial properties and thermodynamic behavior of cationic amphiphilic β-cyclodextrins substituted with one or seven alkyl chains. Issue 76 (29th July 2016) - Baâzaoui, Mondher; Béjaoui, Ines; Kalfat, Rafik; Amdouni, Noureddine; Hbaieb, Souhaira; Chevalier, Yves
Abstract : New cationic amphiphilic β-cyclodextrins (β-CD) were investigated for their surface-active properties and self-association. Abstract : New cationic amphiphilic β-cyclodextrins (β-CD) were investigated for their surface-active properties and self-association. β-Cyclodextrin was mono- or per-substituted at its narrow rim by short (butyl) or long (dodecyl) aliphatic chains. The mono-substituted β-CDs are classical surfactants having a single hydrophobic tail and a single hydrophilic head; the per-substituted β-CDs have seven hydrophobic tails and seven hydrophilic heads. A comparative study of their surface-active properties at air/water and oil/water interfaces and of the formation of aggregates was achieved. All cationic β-CD surfactants show surface activity and self-assemble above a well-defined concentration referred to as the cmc because of the interactions between their hydrophobic tails. The inclusion of the alkyl chain inside the hydrophobic cavity did not cause other types of self-association. Though the main features of the surface-activity look similar to classical surfactants, such amphiphilic β-CDs show several specificities. The short-chained butyl derivatives behave as classical long-chained surfactants do. The head–tail interaction between the long dodecyl chain and the β-CD cavity of mono-substituted β-CD causes the formation of an intramolecular inclusion complex that weakens its hydrophobic character. The seven dodecyl chains of per-substituted β-CD tightly pack together, lowering the contact area with water and weakening their hydrophobic character. Part of the counterions of multi-charged per-substituted β-CD is associated as ion pairs with the cationic groups of the amphiphilic β-CD. A close analogy with the behavior of gemini surfactants is worth noticing.